The Urgency of Setting Criminal Sanctions Against Spreaders of Election Hoaxes - Pramesthi Pranoto, Brigita; Fatmawati Octarina, Nynda (Lafadz Jaya Publisher, 2024)
The increasing development of technology and information provides a number of benefits and negative impacts. The spread of fake news (hoaxes) is one of the cases that often occurs in Indonesia. Perpetrators of spreading fake news use social media as a platform for spreading fake news. Regarding the spread of fake news, it is regulated in Law Number 1946, the Criminal Code, and the ITE Law of 2016. The urgency in several of these policies includes law enforcement factors, the benefits of law for society, as community control, and not giving rise to multiple interpretations and realizing justice. This research uses a type of normative juridical research. The data collection technique used is library research. The analysis used is a normative analysis method. This research shows the urgency of several policies that regulate the spread of fake news in Indonesia.